Assessment of the physicochemical properties of chrysotile-containing brake debris pertaining to toxicity. (3rd July 2019) - Boyles, Matthew S. P.; Poland, Craig A.; Raftis, Jennifer; Duffin, Rodger
Abstract: Grinding and drilling of chrysotile asbestos-containing brake pads during the 20 th century led to release of chrysotile, resulting in varying levels of workplace exposures of mechanics. Despite exposures, excess risk of mesothelioma remains in doubt. Objectives: The toxicity of particulates is primarily derived through a combination of physicochemical properties and dose and as such this study aimed to determine properties of asbestos-containing brake debris (BD) which may influence pathogenicity and potential of mesothelioma. Materials and Methods: Chrysotile-containing brake pads were ground – to reflect occupational activities, aerosolized, and size-fractionated to isolate respirable fractions. Analysis of morphology, biodurability, surface charge, and interactions with macrophages were undertaken. Results: The respirable fraction of BD contained ∼15–17% free chrysotile fibers thereby constituting a small but relevant potential long fiber dose. Acellular biodurability studies showed rapid dissolution and fragmentation of chrysotile fibers that was consistent for pure chrysotile control and BD samples. Conclusions: The long, free, respirable chrysotile fibers were present in BD, yet were of low bio-durability; incubation in artificial lysosomal fluid led to destruction of free fibers.